Mental Health- An Emotional Roller Coaster Around Menopause - Sujitha Pandian; Yashvanthan; Angeline Grace G (National Journal of Community Medicine)
Menopausal mental health is a critical yet often overlooked aspect of a woman’s overall well-being during the menopausal transition. Menopause, which typically occurs between the ages of 45 and 55, marks the end of a woman's reproductive years, characterized by a natural decline in estrogen and other hormones. This hormonal fluctuation can lead to various mental health challenges, including mood swings, anxiety, depression, and cognitive changes like memory lapses or difficulty concentrating.